Dance as world of senses, socio-cosmic order and mobility. Case study of Catholic women in Goa, India - Pereira, C. (2022)
The sensorial and aesthetic dimensions of the songs and dances of the Catholic Gawda women highlight the connection between religion, ritual and touristic performances. On the one hand, in the village, the aesthetics of the ritual’s place acquires symbolic meaning together with the body experience shared by women while dancing collectively—reinforcing their ties through the individual bodies. By learning the dance steps through the imitation of older women in their yearly ritual, the Gawda demonstrate that ‘when sensory orders express cosmic orders, cosmologies are not only learnt through hearing or reading, but lived through the body’. The arrangement of the objects, the space’s combination of nature and sacred symbols, the colours highlighting women’s movements, the sound of their voices—all emphasize the non-verbal dimension of the ritual. On the other hand, during state events or touristic performances the aesthetical references change, and the songs, dances and clothes become standardized and shorter in order to provide identical reproductions for different audiences.